Xanthohumol in Brewing – Impact of Malt, Xanthohumol Dosage, Wort and Storage - Wunderlich, Sascha; Zürcher, Achim; Back, Werner (BrewingScience, 2012)
The enrichment of the hop polyphenol xanthohumol (XN) in beer is limited because it is hardly soluble in water and it isomerises during wort boiling. Commercial dark beers comprise higher XN contents and in first investigations roasted substances proved to have potential for XN enrichment. In our brewing trials (10 and 50 L scale) we examined isomerisation in worts produced with different ratios of roasted malt beer. Moreover, we studied the point in time for XN addition to wort, as well as 23 malt and cereal varieties and a roasted malt liquid for the first time. In order to describe the XN carrier effect in more detail we compared gel permeation chromatograms of Pilsener, caramel, and roasted malt wort. Further, we conducted temperature stability experiments on XN in beer during pasteurisation and storage. The investigations confirm results from previous studies in which substances in dark roasted malts increase the total XN content in wort but still isomerisation takes place during wort boiling. New is the result that late addition of XN and rapid cooling of wort significantly reduce losses by isomerisation in dark brews. Moreover, the XN content increased with an increasing content of roasted substances in ceteris paribus wort. In tests on different malting products, we found an increasing XN enrichment potential with increasing EBC colour of roasted products. Intensively roasted malts contain predominantly high molecular weight (HMW) substances and are most effective for XN enrichment in the brewing process. Caramel malt wort with comparable EBC colour to roasted malt wort contained less XN carrying fractions with decreased XN contents. Stability tests showed that XN is widely stable during pasteurisation. Storage losses of XN increase with increasing storage temperature but decrease with increasing ratios of roasted substances in beer. We conclude that a range of roasting substances possess XN carrying and protective effects. Optimised roasting may improve this effect.